Dynamic Archives Management of the Administration Section at SMK YPLP PGRI 1 Makassar - Hikmah, Nurul; Akib, Haedar; Niswaty, Risma (ASHA Publishing, 2025)
One of the most important pieces of information for an organization is the recording of its activities, which is stored in the form of archives. Because archives play a crucial role, they must be managed effectively and adequately. This study aims to determine the Dynamic Archives Management and the inhibiting factors in the Dynamic Archives Management of the Administration Section at SMK YPLP PGRI 1 Makassar. The approach and type of research used are qualitative research and descriptive research, respectively. The informants include the Head of Administration, the Student Affairs Administration staff, and the archives teacher at SMK YPLP PGRI 1 Makassar. The data collection techniques used are observation, interview, and documentation methods. The data analysis techniques employed are data condensation, data presentation, and drawing conclusions. The results of this study indicate that all indicators used in the study of Dynamic Archives Management in the Administration Section at SMK YPLP PGRI 1 Makassar are classified as having a less exemplary implementation. The indicators in question, recording, and distribution, are still less than optimal. This can be seen from the management of incoming mail that does not follow the procedure. Storage is also less than optimal; this is because the storage space is still inadequate, as evidenced by the unsuitable storage area, the lack of cabinets, and the absence of filing cabinets, as well as the disorganized arrangement of folders. Maintenance is classified as less than good; this can be seen from the maintenance of archives, which is limited to cleaning them of dust. Depreciation is classified as less than good; this can be seen from the fact that depreciation regulations have not implemented depreciation.